Solution Thermodynamics of Sodium Diclofenac in Ethanol + Water Mixtures and Correlation with the Jouyban-Acree Model (2023)
The solubility of sodium diclofenac (NaDIC) in several ethanol + water mixtures was determined at 293.15 K to 313.15 K. The thermodynamic functions Gibbs energy, enthalpy, and entropy of solution were obtained from these solubility data by using the van’